2010
DOI: 10.1002/cjce.20299
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the impact of kraft pulping and bleaching parameters on Eucalyptus camaldulensis pulp properties using MATLAB

Abstract: In this work, Eucalyptus camaldulensis was evaluated as the raw material for chemical pulp under different pulping and bleaching conditions. The pulping was carried out at different H-factors, and at different effective alkalis. The resulting pulps were then oxygen delignified and bleached using various dosages of bleaching chemicals in a D 0 EpD 1 sequence. The effect of independent variables (pulping or bleaching variables) on dependent variables (pulp properties) was analysed based on the multivariable leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The values found in the literature are lower than the ones presented in this manuscript for all the species mainly because we used an exhaustive and sequential extraction with three solvents with different degrees of polarity. For instance the result obtained for E. camaldulensis is above the reported values e.g., Moussaouiti et al (2012) presented 6.7% and 6.6% of hot water and ethanol-toluene extractives, respectively, and Fatehi et al (2010) reported 8.9% of ethanol-benzene extractives. Lignin content for the different species showed a variation in absolute values of 9.2%, from highest (E. resinifera, 30.8%) to lowest (E. maculata, 21.6%) with 85-93% of the total lignin being insoluble lignin (Klason lignin).…”
Section: Pulp Characterizationmentioning
confidence: 53%
“…The values found in the literature are lower than the ones presented in this manuscript for all the species mainly because we used an exhaustive and sequential extraction with three solvents with different degrees of polarity. For instance the result obtained for E. camaldulensis is above the reported values e.g., Moussaouiti et al (2012) presented 6.7% and 6.6% of hot water and ethanol-toluene extractives, respectively, and Fatehi et al (2010) reported 8.9% of ethanol-benzene extractives. Lignin content for the different species showed a variation in absolute values of 9.2%, from highest (E. resinifera, 30.8%) to lowest (E. maculata, 21.6%) with 85-93% of the total lignin being insoluble lignin (Klason lignin).…”
Section: Pulp Characterizationmentioning
confidence: 53%